a) what should be added to x²+xy+y² to obtain 2x²+3xy?
b) What should be subtracted from 2a+8b+10 to get -3a+7b+16?
Answers
Answered by
20
Step-by-step explanation:
a.suppose p be added to x^2+xy+y^2toget2x^2+3xy
=p+x^2+xy+y^2=2x^2+3xy
=p= 2x^2+3xy-(x^2+xy+y^2)
p=2x^2+3xy-x^2-xy-y^2
p=x^2+2xy-y^2
b.suppose x be subtracted from 2a+8b+10to get-3a+7b+16
2a+8b+10-x=-3a+7b+16
-x=-3a+7b+16-(2a+8b+10)
-x=-3a+7b+16-2a-8b-10
-x=-5a-b+6
-(x)=-(5a+b-6)
x=5a+b-6
Answered by
5
(a) (2x2 + 3xy) – (x2 + xy + y2)
= 2x2 + 3xy – x2 – xy – y2
= 2x2 – x2 + 3xy – xy – y2
= x2 + 2xy – y2 is required expression.
(b) (2a + 8b + 10) – (-3a + 7b + 16)
= 2a + 8b + 10 + 3a – 7b – 16
= 2a + 3a + 8b – 7b + 10 – 16
= 5a + b – 6 is required expression.
Similar questions